Rheumatoid arthritis: A major symptom and symptomatic therapy - Yuri Aleskandrovich Olyunin (Современная ревматология)
Pain is a major problem in patients with rheumatoid arthritis (RA). It produces a serious psychological discomfort, causes sleep disorders, and drastically limits physical activity. Pain is one of the main signs of inflammation and its intensity correlates with inflammatory activity. The early use of disease-modifying antirheumatic drugs, regular monitoring, and timely correction of therapy in accordance with the treat-to-target principle make it possible to effectively monitor the activity of RA and to delay its progression. However, despite a marked decrease in RA activity, pain does not go away completely and may increase with time in a number of cases. Pain occurring in patients with RA is always far short of being caused by arthritis. It may be also related to comorbidity, osteoarthritis or fibromyalgia in particular. Pain induced by comorbidity may seriously distort the result of assessment of inflammatory activity and a physician's decision made to correct drug therapy in accordance with the treat-to-target principle.Nonsteroidal antiinflammatory drugs (NSAIDs) are in most common use for the symptomatic therapy of RA. In spite of a significant reduction in pain and stiffness during therapy with NSAIDs, they do not affect the progression of X-ray changes. Virtually all NSAIDs may relieve pain when used in doses substantially smaller than those required to suppress inflammation. NSAIDs are an essential component of combination therapy for RA. They are given just at the early stage of the disease, by taking into account the gastrointestinal tract, kidney, and cardiovascular system. The National Institute for Health and Clinical Excellence in the United Kingdom proposes to administer analgesics (paracetamol and codeine) to reduce needs for NSAIDs in RA. For the time being, the use of analgesics in RA has, however, a weak evidence base.Different trials have also studied the efficiency of monotherapy with weak opioids, but it has proven to be also low. It is well, where possible, to avoid the long-term use of opioids.Along with NSAIDs and paracetamol, the recent guidelines of the International Expert Group of Pain Pharmacotherapy to use tricyclic antidepressants as additional agents to treat joint inflammatory diseases, which may be effective in some cohort of patients, such as those with RA and comorbid depressive disorders.Besides drug therapy, nonpharmacological methods are also successfully used in the treatment of pain in RA. The effective suppression of pain makes it possible not only to considerably reduce existing discomfort in a patient, but also to more correctly choose treatment policy in each specific case.